Non-neglectable therapeutic options for age-related macular degeneration: A promising perspective from traditional Chinese medicine. (10th January 2022) - Li, Yuli; Li, Xing; Li, Xiaoya; Zeng, Zhihong; Strang, Niall; Shu, Xinhua; Tan, Zhoujin
Abstract: Ethnopharmacological relevance: Age-related macular degeneration (AMD) is a chronic neurodegenerative disease which causes irreversible central vision loss among the elderly population. Traditional Chinese Medicine (TCM), including formulas, acupuncture and herbs, has been used in the treatment of AMD for thousands of years and is currently used by many AMD patients around the world. Aim of the review: A comprehensive, in-depth literature review examining the use of TCM in the treatment of AMD has yet to be compiled. This review will improve current knowledge relating to the use of TCM and will open new avenues of exploration in developing new drugs for the treatment of AMD. Methods: A literature search of the PubMed database, Web of Science, Google Scholar and China National Knowledge Infrastructure (CNKI) was performed using relevant terms and keywords related to TCM in the treatment of AMD. Related books, PhD and master's theses were also researched. Results: The TCM-based interpretation of AMD has been used to establish a theoretical foundation for understanding the effect of TCM formulas and acupuncture on AMD. The possible mechanism of action of common Chinese herbs has also been discussed in detail. Conclusion: TCM is a promising treatment option of AMD patients. However, lack of rigorous scientific evidence has limited the impact and uptake of TCM therapy. Future research should focus on improving understanding of the mechanism of action and bioactive components of TCM therapies. Graphical abstract: Image 1